Electrotonic Myofibroblast-to-Myocyte Coupling Increases Propensity to Reentrant Arrhythmias in Two-Dimensional Cardiac Monolayers - Zlochiver, Sharon (The Biophysical Society, 2008)
In pathological conditions such as ischemic cardiomyopathy and heart failure, differentiation of fibroblasts into myofibroblasts may result in myocyte-fibroblast electrical coupling via gap junctions. We hypothesized that myofibroblast proliferation and increased heterocellular coupling significantly alter two-dimensional cardiac wave propagation and reentry dynamics. Co-cultures of myocytes and myofibroblasts from neonatal rat ventricles were optically mapped using a voltage-sensitive dye during pacing and sustained reentry. The myofibroblast/myocyte ratio was changed systematically, and junctional coupling of the myofibroblasts was reduced or increased using silencing RNAi or adenoviral overexpression of Cx43, respectively. Numerical simulations in two-dimensional models were used to quantify the effects of heterocellular coupling on conduction velocity (CV) and reentry dynamics. In both simulations and experiments, reentry frequency and CV diminished with larger myofibroblast/myocyte area ratios; complexity of propagation increased, resulting in wave fractionation and reentry multiplication. The relationship between CV and coupling was biphasic: an initial decrease in CV was followed by an increase as heterocellular coupling increased. Low heterocellular coupling resulted in fragmented and wavy wavefronts; at high coupling wavefronts became smoother. Heterocellular coupling alters conduction velocity, reentry stability, and complexity of wave propagation. The results provide novel insight into the mechanisms whereby electrical myocyte-myofibroblast interactions modify wave propagation and the propensity to reentrant arrhythmias.